Thermodynamics of poly(7-methoxy-2-acetylbenzofurane methyl methacrylate-co-styrene) and poly(2-acetylbenzofurane methyl methacrylate-co-styrene)-probe interactions at different temperatures by inverse gas chromatography - Ilter, Zulfiye; Demir, Abdullah; Kaya, Ismet (Academic Press Ltd- Elsevier Science Ltd, 2016)
In this study, some thermodynamic properties of poly(7-methoxy-2-acetylbenzofurane methyl methacrylate-co-styrene) Poly(MABMM-co-St) and poly(2-acetylbenzofurane methyl methacrylate-costyrene) Poly(ABMM-co-St) were studied by the inverse gas chromatography (IGC) technique. The retention times (t(r)) of selected organic probes were determined from the interactions with Poly (MABMM-co-St) and Poly(ABMM-co-St) of four groups of solvents with different chemical natures and polarities. Then, specific volume (V-g(0)) values of probes were calculated at different column temperatures. The glass transition temperatures (T-g) of Poly(MABMM-co-St) and Poly(ABMM-co-St) were found as 393, 413 K from inverse gas chromatography measurements, respectively. Under the glass transition temperatures adsorption heat (Delta Ha) and above the glass transition molar heat (Delta H-1(S)), free energies (Delta G(1)(S)) and entropies (Delta S-1(S)) belonging to sorption for every probe were calculated from inverse gas chromatography measurements. The partial molar heat (Delta H-1(infinity)), partial molar free energy (Delta G(1)(infinity)), Flory-Huggins interaction parameter (chi(infinity)(12)) and weight fraction activity coefficient (a(1)/w(1))(infinity), values for infinite dilute solutions were calculated for polymer-probe systems. The solubility parameter (delta(2)) of the polymer was obtained from the slope and intercepts of Flory-Huggins interaction parameter (chi(infinity)(12)) graphs with solubility parameters (delta(1)) of probes. (C) 2016 Elsevier Ltd.
Keywords: Poly(7-methoxy-2-acetylbenzofurane methyl methacrylate-co-styrene); Poly(2-acetylbenzofurane methyl methacrylate-co-styrene) inverse gas chromatography; Thermodynamic properties